(untitled) - Phạm, Thái Hưng (Hanoi, 2009)
The purpose of this report is to establish, as much as possible, values of indicators that refl ect the situation of the P135-II communes and households at the onset of the Program.
Keywords: Public welfare,Revolving fund,Nghèo đói,Phúc lợi xã hội,Quỹ quay vòng,Poverty; Government policy,Chính sách nhà nước; Vietnam,Vietnam,Việt Nam,Việt Nam,Việt Nam,Vietnam